Addressing the persistence of Tuberculosis Among the Canadian Inuit Population: The need for a social determinants of health framework - Kulmann, Kassandra C; Richmond, Chantelle A. M. (International Indigenous Policy Journal, 2011)
Canadian Aboriginal people have poorer levels of health than the general population. A serious issue is the high rate of tuberculosis (TB) among the Inuit population; rates are much higher than those of the general Canadian population. Several social determinants of health (SDOH), including household crowding and poverty, are strongly correlated with TB prevalence. In this paper, we describe the medical and social determinants of TB, and critically examine the TB literature specific to the Inuit population. The majority of studies recommend biomedical interventions for the treatment of TB. Few researchers have employed the social determinants of health theory to steer their research, and even fewer researchers suggest improving living and social conditions in Inuit communities as a way of eradicating TB. We conclude with research and policy recommendations.